Formulating The Vision, Mission and Goals of Islamic Educational Institutions by Measuring Evaluation and The Role of LeadershipHIP - Anastasya Rahma Nur Faizah; Nova Fadliana Rahmawati; Mardiyah (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2025)
Islamic educational institutions have an important role to play in leading students to success in the future. To achieve this goal, a clearly formulated vision, mission and objectives are needed and implemented with the right strategy. The leadership of school principals and stakeholders has a role to play in ensuring that the vision and mission are not just a slogan, but also realised in every aspect of education. However, reality shows that many schools face challenges in integrating the vision, mission and goals into educational programs due to the lack of systematic evaluation and weak understanding of stakeholders. This study uses the library research method by collecting and analysing reference sources, such as books, scientific journals, and relevant articles. The study was conducted through literature identification, critical review, and systematic analysis of previous findings. The results show that visionary leadership, structured evaluation, and active participation of all school elements are the main factors in the successful implementation of the vision and mission. Therefore, data-based decision-making strategies and continuous evaluation are needed to improve the effectiveness of education management.